The potential cost savings of utilizing machine data A study of the possibilities of using Real- Time SPC in production for potential cost reduction in a threading process - Lindvall, Hampus; Voljevica, Tarik (My University, 2019)
Machines are becoming more and more complex and the tasks they are expected to complete are of similar complexity. If the machines are expected to take more complex jobs from humans, then they need to become more like humans. The machines need to be adaptable to their surroundings. They need to be able to “see” and adapt to what they “feel”. This intelligence is a cornerstone in the formation of Industry 4.0. The steps to get fully adaptive machines, or as it is called in this report, real-time statistical process control (real-time SPC), is not that far in the future. Can tool breakage be predicted? Is it possible to detect tool wear? What are the potential cost savings if tool breakage and tool wear is predicted? The findings of this thesis showed that only by measuring the torque within the spindle, and predicting the breakage and tool wear, significant payoffs can become a reality. The findings of the interviews along with the conducted analysis of the threading process, showed that predicting thread tap breakage and extending tool life is possible. If the tool life is extended by 25%, the cost savings for only this element is approximately 350 000 SEK annually. If all the thread tap breakages can be prevented and the life length of the tools are extended by 25%, the cost savings are instead approximately at least 600 000 SEK based on numbers from production year 2018. This is without considering the insights gained of the process and the contribution towards designing future systems for Industry 4.0. The value which emerges from taking small steps towards improving and expanding data collection are immense and any manufacturer that values their competitive edge should have started yesterday…Can tool breakage be predicted? Is it possible to detect tool wear? What are the potential cost savings if tool breakage and tool wear is predicted? The findings of this thesis showed that only by measuring the torque within the spindle, and predicting the breakage and tool wear, significant payoffs can become a reality. The findings of the interviews along with the conducted analysis of the threading process, showed that predicting thread tap breakage and extending tool life is possible. If the tool life is extended by 25%, the cost savings for only this element is approximately 350 000 SEK annually. If all the thread tap breakages can be prevented and the life length of the tools are extended by 25%, the cost savings are instead approximately at least 600 000 SEK based on numbers from production year 2018. This is without considering the insights gained of the process and the contribution towards designing future systems for Industry 4.0. The value which emerges from taking small steps towards improving and expanding data collection are immense and any manufacturer that values their competitive edge should have started yesterday…
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics